MERGHERS pilot: MeerKAT discovery of diffuse emission in nine massive Sunyaev–Zel'dovich-selected galaxy clusters from ACT. Issue 2 (5th April 2021) - Knowles, K; Pillay, D S; Amodeo, S; Baker, A J; Basu, K; Crichton, D; de Gasperin, F; Devlin, M; Ferrari, C; Hilton, M; Huffenberger, K M; Hughes, J P; et al.
ABSTRACT: The MeerKAT Exploration of Relics, Giant Halos, and Extragalactic Radio Sources (MERGHERS) survey is a planned project to study a large statistical sample of galaxy clusters with the MeerKAT observatory. Here we present the results of a 16-h pilot project, observed in response to the 2019 MeerKAT Shared Risk proposal call, to test the feasibility of using MeerKAT for a large cluster study using short (0.2–2.1 h) integration times. The pilot focuses on 1.28-GHz observations of 13 massive, low-to-intermediate redshift (0.22 < z < 0.65) clusters from the Sunyaev–Zel'dovich-selected Atacama Cosmology Telescope (ACT) DR5 catalogue that show multiwavelength indications of dynamical disturbance. With a 70 per cent detection rate (9/13 clusters), this pilot study validates our proposed MERGHERS observing strategy and provides twelve detections of diffuse emission, eleven of them new, indicating the strength of MeerKAT for such types of studies. The detections (signal-to-noise ratio ≳ 6) are summarized as follows: two systems host both relic(s) and a giant radio halo, five systems host radio haloes, and two have candidate radio haloes. Power values, k -corrected to 1.4 GHz, assuming a fiducial spectral index of α = −1.3 ± 0.4, are consistent with known radio halo and relic scaling relations.